2009
DOI: 10.1097/mot.0b013e3283186fc1
|View full text |Cite
|
Sign up to set email alerts
|

Development of insulin-producing cells from primitive biologic precursors

Abstract: Purpose of review The differentiation of pluripotent and multipotent stem cells into insulin producing cells has the potential to create a renewable supply of replacement β cells with tremendous utility in the treatment of diabetes. The purpose of this review is to summarize recent advancements in the field, with emphasis on the limitations of this technology as it relates to the β cell. Recent findings Multiple groups have developed successful in vitro protocols to differentiate human embryonic stem cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…Biological research on stem and islet cells has led to the development of experimental islet cell replacement using harvested islets and efforts to solve this problem using islets grown from stem cells therapy [8,9]. The signals necessary for effective promotion of islet beta-cell development must be identified for stem cells therapy to become an effective treatment, or even a cure, for T1DM and a treatment option for type 2 diabetes mellitus (T2DM) [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological research on stem and islet cells has led to the development of experimental islet cell replacement using harvested islets and efforts to solve this problem using islets grown from stem cells therapy [8,9]. The signals necessary for effective promotion of islet beta-cell development must be identified for stem cells therapy to become an effective treatment, or even a cure, for T1DM and a treatment option for type 2 diabetes mellitus (T2DM) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The signals necessary for effective promotion of islet beta-cell development must be identified for stem cells therapy to become an effective treatment, or even a cure, for T1DM and a treatment option for type 2 diabetes mellitus (T2DM) [8,9]. Our laboratory has successfully isolated and characterized a population of fetal pancreatic progenitor cell (PPC) model from first trimester human fetal pancreas using a basic protocol developed for differentiating PPCs into insulin-secreting islet-like cell clusters (ICCs) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…There have been impressive advances in the derivation of ␤-like cells from human ES cells that provide great hope that such an approach may one day offer a plentiful source of ␤-cells for transplantation (95,96). There continues to be remarkable progress in this field, including the identification of small molecules that promote the differentiation of human ES cells into pancreatic progenitor cells (97).…”
Section: Conclusion and Other Considerationsmentioning
confidence: 99%
“…Moreover, no in vivo experiment with encapsulated pluripotent stem cells have been reported. Nevertheless, in animal studies, often with immunodeficient animals, these cells showed a high therapeutic potential and were used for the treatment of diabetes, spinal cord injury and visual impairment by creation of new insulin-producing cells, neurons and retinal cells, respectively [35][36][37]. Pluripotent stem cells have also been investigated in animal models concerning several diseases such as Parkinson's disease, muscular dystrophy and heart failure [38][39][40].…”
Section: Controlled Expansion Cultivation and Differentiation Of Mesmentioning
confidence: 99%